Drawing a Roadmap for Reforming Oil Pricing Policy - Kojima, Masami (World Bank, Washington, DC, 2014)
Between 2003 and 2012 the average annual world prices of gasoline, diesel, and kerosene in 160 countries more than doubled, while the prices of liquefied petroleum gas (LPG) used for cooking and heating increased by two-thirds. Between January 2009 and January 2013, many countries did not pass through increases in world oil product prices to domestic consumers. The median pass-through for gasoline and diesel increased with income and was less than two-thirds in low- income countries. High-income countries had larger median pass-through coefficients than any other income group. For kerosene, the median pass-through was full in upper-middle-income countries, but half in low and lower-middle-income countries. Among developing countries, the median pass-through for LPG was highest in low-income countries. More generally, about two thirds of the study countries have kept domestic prices below market-based levels for one or more fuels in the past three years, subsidizing consumers. In every case the government pays directly-or indirectly through budgetary transfers, tax expenditures, or lower corporate tax collection due to financial losses suffered by oil companies. Many countries have universal price subsidies, widely acknowledged to be regressive. Quite a few have subsidies targeting certain consumer categories, most notably kerosene and LPG for households. Targeted subsidies for oil products have large leakages (such as diversion and smuggling) because, unlike electricity or natural gas, liquid fuels are easy to store and transport. Differentiating prices for the same oil product by user category creates powerful financial incentives to divert lower-priced fuels to users ineligible for the price discounts. Typical recipients of such targeted price subsidies are households (kerosene or LPG for cooking, lighting, and heating), transport operators, farmers, and fishermen. Although prices of kerosene and diesel are close on the world market, many governments price kerosene below diesel in the name of protecting non-electrified households that use kerosene for cooking, lighting, and heating. Government transparency is important regarding the agency in charge of pricing, the scope of its regulatory power, how prices are set, the criteria for price adjustments, the price breakdown, the magnitude of under-or-over recoveries, and the stakeholders being consulted.